ENTREPRENEURSHIP, INNOVATION AND LEADERSHIP IN MECHANICAL ENGINEERING (Journal of Industrial and Mechanical Engineering, 2020)
Specific competencies and skills of mechanical engineering activities, developed by three entrepreneurship companies in Non-Destructive Testing (NDT), Heat Treatments of Steels, and Special Welds, applied to problems of the national industrial sector, are analyzed, directly involving real examples of innovation and leadership.While emphasizing the evolution of one of the companies, through the innovation and development of NDT techniques, until taking the lead in the Central American region and part of the Caribbean, reference is made to the processes of technology applied in form interactive, by the three companies, in the practice of curative maintenance and applied "on-site" research, with optimal results.It describes the procedures developed, in accordance with the emerging needs of curative maintenance of high-scale production  companies, with the use of techniques available at the time.Subsequently, reference is made to innovative techniques used for problems solving.
Keywords: non-destructive testing; heat treatments; welding; liquid penetrant methods; magnetic particles